Auricular Defects: Autogenous Vs Prosthetic Reconstruction - Gupta, Shubhankur; Gupta, Sugandha; Pandey, Anil (International Journal of Medical Research and Review, 2016)
Introduction: Auricular defects and deformities include not only acquired defects attributable to trauma, burns, tumors, piercing defects, scars, and inflammation/allergies, but also congenital auricularmalformations. Methods: Alternatives for auricular reconstruction include autologous costal cartilage graft, prosthetic reconstruction with adhesives and osseointegrated implants. Conclusion: Total auricular reconstruction in patient with auricular defects is one of the most challenging problems faced by a reconstructive surgeon as it demands precise surgical technique combined with artistic creativity. Ear reconstruction requires carefully planned procedures. The use of autogenous rib cartilage is the gold standard for microtia reconstruction. Overcoming the limitations of surgical procedures prosthetic rehabilitation can be done successfully. The purpose of this article is to compare the two procedures and discuss their advantages and disadvantages.